Urban Agricultural Revolution in Japan with Verticulture Technology - Ahmya Ayaka; Fujita Hanako; Hide Haruka (Yayasan Adra Karima Hubbi, 2024)
Urban agriculture is gaining traction as a viable solution to food security challenges and environmental sustainability in densely populated cities. With its limited arable land and high urbanization rate, Japan is at the forefront of adopting innovative agricultural practices. Verticulture technology, which involves vertical farming techniques, offers a promising approach to maximizing food production in urban settings while minimizing land use. This study aims to explore the impact of viticulture technology on urban agriculture in Japan. The research evaluates how vertical farming can enhance food production efficiency, reduce environmental impact, and contribute to sustainable urban development. A mixed-methods approach was employed, combining quantitative and qualitative research methods. Data were collected through field experiments in urban vertical farms, surveys of urban farmers, and analysis of production records. Key performance indicators such as crop yield, resource use efficiency, and environmental impact were measured. Additionally, interviews with urban agriculture experts provided insights into viticulture technology's practical implementation and benefits. The findings indicate that viticulture technology significantly improves crop yields and resource use efficiency compared to traditional urban farming methods. Vertical farms demonstrated up to a 30% increase in yield per square meter and a 50% reduction in water usage. The environmental impact was also reduced, with lower greenhouse gas emissions and minimal land use. Survey responses and expert interviews highlighted the technology's potential to support food security and sustainable urban living. Verticulture technology offers a transformative approach to urban agriculture in Japan, enhancing food production efficiency and sustainability. The significant improvements in crop yields, resource use, and environmental impact underscore the potential of vertical farming to address urban food security challenges. Further research and investment in viticulture technology are recommended to optimize its implementation and maximize its benefits for urban development.